(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article presents the results of many years of research on the winter hardiness of 58 varieties of modern garden roses in the conditions of the Chui Valley.